Hinterland Forces: Architectural Responses at the Margins. (1st July 2022) - Andersen, Angela
Marginalized communities use, adapt, and produce architectures in hinterland spaces in response to geographical, environmental, social, nationalist, and other political forces. Scholarly discourse and approaches to architectural practice may likewise be formed and coerced through marginalization. The hinterland, as the outlying territory beyond the urban or geographical centre, is the physical manifestation of these forces that shape the social margins. At times, architecture is itself a marginalizing actor, and at others, it becomes the site of resistance and negotiation, providing spatial agency and autonomy, and facilitating distributive justice in regard to services and resources. In the hinterland, new architectures are created, pre-existing spaces are destroyed and re-made, and movement, change, and adaptation are given momentum. This article introduces the special issue on hinterland forces. I categorize architectural responses, both in architecture made and used by those in power to control marginal populations, and created by and for marginalized people. This is followed by a summary of the multi-field perspectives and scholarly methods of the contributing authors. The discussion focuses on architectural matters relevant to Islamic societies in several global regions, but the socio-spatial questions and associated responsibilities are relevant to practitioners and scholars in all architectural fields.